CHARACTERISTICS OF REFINED CARRAGEENAN FROM Eucheuma spinosum WITH POTASSIUM HYDROXIDE SOLVENT USING MICROWAVE ASSISTED EXTRACTION (MAE) METHOD IN VARIOUS EXTRACTION TIMES - Yanu Andhiarto; Nurita Pusparini (Jurnal Ilmiah Farmako Bahari, 2025)
Extraction time with Microwave Assisted Extraction (MAE) influences the yield and quality of Carrageenan from Eucheuma spinosum. This research aims to determine the effect of extraction time using microwave-assisted extraction (MAE) on the yield value and quality parameters of E. spinosum carrageenan, including water content, ash content, sulfate content and viscosity. E. spiosum was extracted using 0.5% NaOH base with the microwave-assisted extraction (MAE) method at varying extraction times of 2 minutes, 5 minutes and 8 minutes. The filtrate was filtered and precipitated with ethanol, drying and grinding until a fine carrageenan powder was obtained. Extraction time affected the yield where an increase in the average yield was received along with the length of extraction time. The highest yield in the 8-minute extraction was 17.62% ±0.368. Extraction time also influences the water content and viscosity of the obtained carrageenan but does not affect the extracted carrageenan's ash or sulfate content.